Employee Recruitment At Maesa Ponorogo Hotel Islamic Economic Perspective - Ahmad Ismi Muhaimin; Fitra Rizal (Niqosiya: Journal of Economics and Business Research, 2024)
Introduction: Recruitment is essential in human resource management because it is the first step in finding suitable employees to fill vacant positions. Managers are responsible for managing human resources, so a fair attitude is vital. Good recruitment can increase a positive image and profits for the company. This research aims to analyze the implementation and impact of employee recruitment at the Maesa Ponorogo Hotel from an Islamic economic perspective. Research Methods: The type of research used by researchers is field research, while the method used in this research is qualitative. Results: This research shows that Hotel Maesa Ponorogo places integrity and fairness as a top priority by Islamic recruitment principles so that every candidate has an equal opportunity to be assessed based on their qualifications and potential. This process affects the quality of service to customers and creates a productive and harmonious work environment for employees. Thus, Hotel Maesa Ponorogo's employee recruitment policy reflects their commitment to providing high-quality services, which strengthens the company's positive image and increases overall customer satisfaction, contributing to increased profits for Hotel Maesa.